The Value of Adding Sciatic Block to Continuous Femoral Block for Analgesia After Total Knee Replacement. Issue 2 (1st March 2005) - Pham Dang, Charles; Gautheron, Etienne; Guilley, Jérôme; Fernandez, Modesto; Waast, Denis; Volteau, Christelle; Nguyen, Jean Michel; Pinaud, Michel
Abstract : Background and Objectives: The benefit of adding a sciatic nerve block to the femoral block to improve analgesia after total knee replacement is controversial. The aim of this study is to address this controversy in a prospective, comparative, and randomized study. Methods: Patients were allocated randomly to receive a continuous femoral nerve block or continuous blocks of both the femoral and sciatic nerves. Stimulating catheters were used in all cases. A loading dose of 15 mL ropivacaine 0.75% was injected into each catheter, followed by administration of ropivacaine 0.2% (2-5 mL/h infusion via the femoral catheter; bolus 10 mL repeated every 12 hours in the sciatic catheter). The primary outcome was visual analog scale (VAS) scores (0 = no pain, 100 mm = worst pain) in postanesthesia care unit and in the 48-hour period after surgery. The secondary outcomes were amplitude of knee flexion, morphine consumption, and occurrence of postoperative nausea and vomiting (PONV). Results: The VAS scores at rest were significantly higher when there was only continuous femoral nerve block than when there was both continuous femoral and sciatic nerve blocks. This difference progressively decreased and disappeared at 36 hours after surgery. The combined femoral and sciatic blocks decreased the morphine consumption by 81% and significantly decreased the occurrence of PONV. Conclusion: During the 36 hours immediately after total knee replacement, the combination of continuous femoral and sciatic nerve blocks improves analgesia while decreasing morphine consumption and PONV.